The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12870-020-02344-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic analysis provides insights into anthocyanin and procyanidin accumulation in pear

Abstract: Background: Pear is one of the most important fruit crops worldwide. Anthocyanins and procyanidins (PAs) are important secondary metabolites that affect the appearance and nutritive quality of pear. However, few studies have focused on the molecular mechanism underlying anthocyanin and PA accumulation in pear. Results: We conducted metabolome and transcriptome analyses to identify candidate genes involved in anthocyanin and PA accumulation in young fruits of the pear cultivar 'Clapp Favorite' (CF) and its red … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 63 publications
(88 reference statements)
0
48
0
Order By: Relevance
“…However, from another perspective, it is because of the great difference in the material background that we can obtain more, and more valuable target genes and metabolites. This conclusion is backed up by many studies [ 49 52 ]. As far as our results are concerned, I think the DEMs and DEGs that we have screened for are fairly reliable.…”
Section: Discussionmentioning
confidence: 77%
“…However, from another perspective, it is because of the great difference in the material background that we can obtain more, and more valuable target genes and metabolites. This conclusion is backed up by many studies [ 49 52 ]. As far as our results are concerned, I think the DEMs and DEGs that we have screened for are fairly reliable.…”
Section: Discussionmentioning
confidence: 77%
“…Plant metabolomic analysis enables us to study the relationship between metabolites produced by biological processes and plant characteristics [ 21 ]. Flavonoids are vital pigments for regulating the rind color of many fruits [ 11 , 19 , 22 ]. There are six main types of flavonoids in plant tissues: flavones, isoflavones, flavonols, flavanones, flavanols, and anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…Another important study in strawberry identified three genes, chalcone synthase ( CHS ), dihydroflavonol reductase ( DFR ), and flavonol 3- O -glucosyltransferase ( F3H ), as well as three anthocyanin metabolites, cyanidin 3- O -glucoside chloride, cyanidin 3-galactoside, and cyanidin 3-glucoside, that are involved in the red fruit color [ 10 ]. Combining transcriptome and metabolome approaches, Zhang et al [ 11 ] revealed that the red mutation cultivar ‘Red Clapp Favorite’ of pear was caused by the PcGSTF12, which was involved in anthocyanin and procyanidin accumulation. Recently, γ-carotene, CRTISO , and ε-LCY were identified as candidates involved in the orange pigmentation in Liriodendron tulipifera [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, heterologous expression of pear PcGSTF12 in the Arabidopsis tt19 mutant showed that PcGSTF12 did not complement the mutant seed color to the normal brown, but it promoted the procyanidin A3 accumulation in the mutant and affected the transcription of PAs-and anthocyanin-related genes. The results of this study indicated that PcGSTF12 may be involved in the transport and accumulation of PAs and anthocyanins [79].…”
Section: Structure and Biosynthesis Of Proanthocyanidinsmentioning
confidence: 65%